Examining the effect of mindfulness-based art therapy (MBAT) on stress and lifestyle of Iranian pregnant women. (17th August 2020) - Jalambadani, Zeinab; Borji, Abasalt; Bakaeian, Mehdi
Abstract: The purpose of this study was to determine the effect of mindfulness-based art therapy (MBAT) in decreasing stress and improving on pregnant women's life style in Neyshabur, Iran 2018. The participants of the present quasi-experimental study were 84 pregnant women. The findings showed that the MBAT group demonstrated a significant decrease in symptoms of distress and significant improvements in key aspects of the health-related style of life as measured by Health Promoting Lifestyle Profile-II questionnaire. Moreover, it was found that the MBAT intervention had a significant effect on improving lifestyle behaviours ( p  < .05). The highest mean score of lifestyle was for the sub-domain of nutrition (31.35 ± 5.34), while the lowest score was achieved by the sub-domains of physical activity (13.55 ± 1.89).The mean (SD) score of stress management was (19.12 ± 1.54). This investigation of MBAT provides initial encouraging data that support a possible future role for the intervention as a psychosocial option for decreasing symptoms of distress in pregnant women and improving their lifestyle. Impact statement: What is already known on this subject? Mindfulness-based art therapy is a blend of basic meditation principles and art therapy. The results of this study showed that mindfulness-based art therapy (MBAT) could decrease the stress and improve lifestyle behaviours in pregnant women. What do the results of this study add? The results of the present study showed that mindfulness-based art therapy (MBAT) during pregnancy decreased the stress and improved life style. It is believed that changing lifestyle to include mind-body medicine such as MBAT in pregnant women will greatly reduce stress responses, and help protect pregnant women from disease during pregnancy. What are the implications of these findings for clinical practice and/or further research? The study showed the important role of mindfulness-based art therapy (MBAT) during pregnancy in reducing stress and improving life style.